Students' Perception of Outdoor Learning Method in Speaking Skill at Mubaroq English Course - Dina Mauliya; Siti Maria Ulfa (Global Action and Education for Society, 2025)
Speaking skills have a very important role, especially in the context of language education. Good speaking skills will have a positive impact on students' future. But in reality, some students' speaking skills are not good. Therefore, teachers need to create an environment that supports and facilitates the development of students' speaking skills. Teachers use outdoor learning methods to achieve learning objectives. The success of the learning process can be seen from the positive responses given by students. This study aims to explore students' perceptions of outdoor learning, particularly in the context of speaking skills and to provide useful information for teachers and further researchers. This research was conducted at Mubaroq English Course. To conduct this research, the researcher used a qualitative approach, in which students' responses were interpreted in depth. Data collection was conducted through interviews involving four students from basic class. The results of the study showed a positive impact on students' speaking skills, where they became more confident, brave, and able to interact with their surroundings. This also contributes to the development of their social interactions. Outdoor learning methods can be used as an effective and interesting learning alternative.